6(2+x)=4(3-x)

Simple and best practice solution for 6(2+x)=4(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2+x)=4(3-x) equation:


Simplifying
6(2 + x) = 4(3 + -1x)
(2 * 6 + x * 6) = 4(3 + -1x)
(12 + 6x) = 4(3 + -1x)
12 + 6x = (3 * 4 + -1x * 4)
12 + 6x = (12 + -4x)

Add '-12' to each side of the equation.
12 + -12 + 6x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
0 + 6x = 12 + -12 + -4x
6x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
6x = 0 + -4x
6x = -4x

Solving
6x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
6x + 4x = -4x + 4x

Combine like terms: 6x + 4x = 10x
10x = -4x + 4x

Combine like terms: -4x + 4x = 0
10x = 0

Divide each side by '10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| m+3n=12 | | 6x^2-23x+7= | | 2j=222 | | 4.87=n+0.87 | | x=-16t^2+400 | | 6p-27-53=4 | | 5.4=t+(-6.1) | | 2(n+1.5)=4.5 | | 117.345+m=200 | | 4v^2-14v-15= | | 9x-5=2x+16 | | -58.109=v-47.736 | | 2x^2+.25x=0 | | -27-53+4=6x | | -0.08=f+0.07 | | -7(t+3)=0 | | a(2a^2+3)+(a^2-10)= | | -x=0.12 | | 6.21=e+(-3.48) | | 4x+8=2x-1 | | 4x-10=95 | | -13.8=h+15.603 | | -176=7x+4(-7x-2) | | 47+5k=9(k+3) | | 2(9-8)= | | -165=-3x+6(-x-11) | | -22=p+13.7 | | 3(x-2)+46=-2x | | k-263.48=-381.09 | | 9c-3c=-8 | | x-19.7=17.48 | | 2x+4(2x-5)=-110 |

Equations solver categories